PAY FOR PERFORMANCE: SOUTH EAST ASIA CROSS COUNTRIES COMPARATIVE STUDY - Yeong, Hui Yan (2011)
Executive pay and company performance has received much attention and debate after the recent credit crisis. Policy makers and the public have since demanded for the executive pay to be regulated and to be more tightly aligned to the company performance. Scholars and economists however, have argued that the existing pay structure is not the cause of the recent credit crisis and thus need not to be over regulated. This paper thus aims to provide deeper understanding on the link between pay and performance by investigating the relation between pay and performance across five different countries, namely Singapore, Malaysia, Indonesia, Thailand and Philippines in the region of South East Asia. This paper also aims to identify a set of corporate governance and public governance mechanisms which are associated with higher pay level in the region. The scope of this paper is set to focus only in the region of South East Asia as it is found that the region is lagging behind with only a few empirical researches that review on the pay and performance relation in the region as compared to other regions in the world. Data was collected from public listed companies in the five countries using Thomson Reuters Datastream and individual annual reports. Panel data analysis was used to analyze the collected data. The results indicate that the pay and performance link in the region is either insignificant or weak. Firm size is the only variable found to be significantly related to the pay level in all of the countries observed. Other variables such as transparency level and board ratio (the ratio of independent directors over the total number of directors) are found to be significantly related to pay level only in certain countries while board size and external auditors are found to have insignificant relation to pay level in either of the country. Public governance indexes such as the integrity index released through Global Integrity Report and the Corruption Perception Index (CPI) released by Transparency International were used to further explain the pay and performance relation in the region.